Optimalisasi Pengajaran Al-Quran dan Hadis melalui Teknologi Kecerdasan Buatan: Tantangan dan Strategi Integrasi - Nur Afif; Adlan Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Artificial Intelligence (AI) technology has revolutionized various fields, including Islamic education, by offering new opportunities to enhance the teaching methods of the Qur'an and Hadith. This article explores how AI can optimize the learning of the Qur'an and Hadith by introducing innovations in teaching methods, as well as identifying the associated challenges and benefits. The main focus is on practical steps to integrate AI harmoniously with religious values, emphasizing the importance of continuous evaluation, feedback from students and educators, and collaboration between educational institutions and training centers. With this approach, AI technology can become an effective tool in supporting holistic and inclusive Islamic education.